Preclinica studies of the combination of EM1 calcitrol analogue with paclitaxel in TNBC - Guevara, Josefina Alejandra (2018)
Triple negative breast cancer (TNBC) does not respond to current targeted therapies as it lacks the expression of hormone receptors and epidermal growth factor receptor HER2. Therefore, current treatment options include cytotoxic drugs such as taxanes, which are limited in terms of extending patient survival or improving patient’s quality of life. The vitamin D receptor is a nuclear transcription factor whose natural ligand, calcitriol, has antitumor activity. Unfortunately, calcitriol anticancer utility is limited by its hypercalcemic effects and thus, vitamin D analogues are being developed to try to solve this problem. We hypothesize that the analogue of calcitriol, EM1, has synergistic effect with Paclitaxel in TNBC without exerting additional toxicity. This would allow to use lower doses of cytotoxic chemotherapy, with the consequent reduction of adverse effects. Also, this combination could minimize or slow the development of resistance to chemotherapeutic agents. We first studied the activity of EM1 on cell count and observed that EM1 strongly decreases the viability of the 4T1 TNBC murine cell line (p<0.001), while not affecting significantly that of MDA-MB-231 cells. In addition, EM1 was able to retard 4T1 cell migration in the wound healing assay (p<0.001) and to inhibit the invasion through Matrigel (p<0.001). The subsequent combination assays showed that EM1 and Paclitaxel did not display antagonistic effects in the cell count of the MDA-MB-231 cells. In addition, a pilot experiment of syngeneic transplantation of 4T1 cells in Balb/C mice showed that mice did not develop hypercalcemia or other signs of toxicity, following 30 days of EM1 treatment. Importantly, although no reduction in the growth of the primary tumor was observed, a significant decrease in the number of lung metastases (p<0.0024) was obtained. Altogether, these results suggest that EM1 could be an effective agent in combination with Paclitaxel in TNBC, by targeting the metastatic process.